CZEGO POWINNIŚMY UCZYĆ A CZEGO UCZYMY – ROZWAŻANIA O EDUKACYJNYCH ZŁUDZENIACH - Zawadzka-Bartnik, Elżbieta (Neofilolog, 2019)
The aim of this article is to point out significant differences between the planned goals of education and their current implementation as indicated by research in schools (by students and teachers) and in institutions of further education which prepare future teachers for the profession. I refer to the notion of the “hidden curriculum” and its influence on students and teachers, which are (among others): an instrumental approach to the teaching and learning process, curricular and organizational inadequacies, and our unconscious attitudes, which are the essential cause of educational illusions. The article ends with suggestions on how to improve effectiveness in education.